Brain hemorrhage detection using hybrid machine learning algorithm - Iqbal, Khondoker Nazia; Azad, Istinub; Emon, Md. Imdadul Haque; Amlan, Nibraj Safwan; Aporna, Amena Akter (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.